1995
DOI: 10.1111/j.1442-200x.1995.tb03362.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte subpopulations in children with vitamin D deficient rickets

Abstract: Recent studies have shown 1,25(OH)2D3‐mediated modulation of the immune system. We examined lymphocyte subpopulations of 16 children with nutritional rickets. Most of the patients suffered more frequent infection episodes than the control group of 15 healthy children and low serum levels of 25OHD and 1,25(OH)2D, such as 38.2 ± 8.6 ng/mL and 15.7 ± 2.6 pg/mL respectively. This decrease correlated with a significant decrease in total T lymphocytes and an increase in B lymphocytes expressing surface IgA, IgM, IgG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 11 publications
1
11
1
Order By: Relevance
“…12 1,25(OH)2D 3 plays an important role in immune modulation. 11 It was noted that most of the children 38(70.4%) were exclusively breast fed up to six months and none of them received vitamin D supplements, these results are comparable with other studies. 13,14 .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…12 1,25(OH)2D 3 plays an important role in immune modulation. 11 It was noted that most of the children 38(70.4%) were exclusively breast fed up to six months and none of them received vitamin D supplements, these results are comparable with other studies. 13,14 .…”
Section: Discussionsupporting
confidence: 80%
“…Yener et al have reported more episodes of bacterial infections in children with vitamin D deficiency as compared to healthy children. 11 In fact T and B lymphocytes have receptors for 1,25(OH)2D. Vitamin D deficiency may predispose to different bacterial infections including pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…(5758) Severe vitamin D deficiency is reported to be related to susceptibility to upper respiratory tract infections(59), tuberculosis(60) and infection in general. (6162) A meta-analysis of 18 trials involving 57,311 subjects, demonstrated a 7% reduction of all-cause mortality in those supplemented with vitamin D.(5) These observations and others suggest that vitamin D deficiency is likely to play a key role in infection, and cardiac and metabolic dysfunctions in critically ill patients.…”
Section: Discussionmentioning
confidence: 96%
“…(33) In another study, patients with severe vitamin D deficiency were abnormally susceptible to infections such as tuberculosis(34) and infection in general. (3536) Similarly, in a Meta-analysis of 18 trials involving 57,311 randomly assigned subjects, Autier found that vitamin D supplementation reduced all-cause mortality by 7% (CI, 1% to 13%). (5) These observations and others suggest that hypovitaminosis D is likely to play a key role in infection, and cardiac and metabolic dysfunctions in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%